Microhole Creation in FDM-Printed Sheet Polymers: A Punching Process Approach - Agus Salim, Urip; Abdullah, Bulan; Suyitno; Pratama, Juan; Badranaya, Muhammad Imawan; Wijaya, Rahman; Mahardika, Muslim; Arifviyanto, Budi (Faculty of Engineering and Technology, Sampoerna University, 2024)
Fused deposition modeling (FDM) 3D printing is one of the additive manufacturing processes that can make components with complex shapes, require no tools, are cheap, safe, and have minimal waste. Despite all the advantages of the FDM process, the inability of this technique to create holes on a micro scale can be a problem and limits its application. In this research, a combination of FDM and machining processes was carried out, where micro holes in FDM printed components were created using a punching process. The punching process is carried out by varying pressure and speed. Furthermore, the diameter of the hole and the quality of the sheared edge of the hole resulting from the punching process were evaluated through observation using an optical microscope. The results show that the holes resulting from the punching process have a better shape and diameter than the FDM process. Then, the analysis of the sheared edge from punching shows that pressure and speed significantly affect the surface quality of the resulting sheared edge, where the quality increases with increasing pressure and speed. In the end, the punching process was proven to create micro-scale holes in FDM-printed polymer, especially at minimum thickness.